Testing a Model of Suicidality in Community Adolescents: A Brief Report - Campos, Rui C. (2015)
We tested a theory-based model of suicidality in adolescents that included the variables: self-criticism, dependency, anger-temperament, depression and anger-in. A sample of 263 adolescents, 107 boys and 156 girls, aged between 15 and 19 years (M=16.8 , SD=1.26), from two high schools in the district of Évora, Portugal, responded to a socio-demographic questionnaire, to the Depressive Experiences Questionnaire for Adolescents (Blatt et al.), the Center for the Epidemiologic Studies of Depression Scale (Radloff), the State -Trait Anger Expression Inventory (Spielberger) and the Suicide Behaviors Questionnaire – Revised (Osman et al.). The model tested by Structural Equation Modeling fits the data well. Self-criticism, dependency and anger-emperament demonstrated indirect relationships with suicidality and depression presented a direct relationship with suicidality and tended to relate indirectly with suicidality through anger-in.